Quality of Solid Organic Fertilizers for Duck Manure and Trembesi Leaves with Papaya Peel Bioactivator - Firdausi, Musdhalifah Husna; Asngad, Aminah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Organic fertilizers can replace inorganic fertilizers that are not environmentally friendly. Duck manure and trembesi leaves can be used as raw materials for fertilizer. Adding local papaya peel microorganisms can help the decomposition process of organic fertilizers. This study aims to determine the quality of solid organic fertilizer made from duck manure and trembesi leaves by adding local papaya peel microorganisms as bioactivation. This study used a completely randomized design (CRD) with a factorial pattern and was repeated three times. The treatment factors are as follows: Factor 1 Raw materials (B1 = Duck Manure 300g: 200g Trembesi Leaves. B2 = Duck Manure 200g: 300g Trembesi Leaves). Factor 2 Papaya Peel Local Microorganisms (P1 = Papaya Peel Bioactivator 25 ml, P2 = Papaya Peel Bioactivator 30 ml). The results showed the best sensory quality in the B2P2 treatment; the fertilizer was blackish brown, smelled of soil, had a crumbs texture like soil, and had a pH of 7. The highest Nitrogen and Phosphorus content was found in the B1P2 treatment, while the highest Potassium content was in the B2P1 treatment. Thus, the quality of solid organic fertilizer is by SNI 19-7030-2004.